The Influence of Human Resource Competence, Accounting Information Systems, Financial Management Accountability, and Audit Quality on the Quality of Financial Reports at PT. Bahari Gembira Ria - Nurmadia, Nurmadia; Afrizal, Afrizal; Erwati, Misni (Faculty of Economics and Business Universitas Jambi, 2025)
This study aims to analyze and empirically examine the influence of Human Resource Competence, Accounting Information Systems, Financial Management Accountability, and Audit Quality on the Quality of Financial Reports at PT. Bahari Gembira Ria. The research employs a quantitative approach with a total of 45 respondents, and data were collected through the distribution of questionnaires. Data analysis methods include Statistical Analysis, Outer Model, Inner Model, and Hypothesis Testing using Partial Least Squares (PLS) analysis assisted by SmartPLS software version 4.1.1.2. The proposed hypotheses state that Human Resource Competence, Accounting Information Systems, Financial Management Accountability, and Audit Quality affect the Quality of Financial Reports. The results indicate that partially, Human Resource Competence and Accounting Information Systems do not affect the Quality of Financial Reports, whereas Financial Management Accountability and Audit Quality have a significant effect. Simultaneously, Human Resource Competence, Accounting Information Systems, Financial Management Accountability, and Audit Quality collectively influence the Quality of Financial Reports at PT. Bahari Gembira Ria.